Study on a Trans-Inverse High Gain SEPIC-Based DC-DC Converter With ZCS Characteristics for Photovoltaic Applications - Mahdi Elmi; Mohamad Reza Banaei; Hadi Afsharirad (International Transactions on Electrical Energy Systems)
This paper aims to propose, study, and implement a non-isolated trans-inverse high step-up SEPIC-based DC-DC converter for photovoltaic applications. To increase the output voltage level, the presented configuration utilizes a three-winding coupled inductor and an improved voltage multiplier cell. However, unlike other coupled inductor-based DC-DC structures, the voltage gain could be enhanced by raising and lowering the secondary and tertiary winding turns ratio, respectively. Furthermore, a passive voltage clamp is employed to reduce the voltage stress on the switch and recover the energy stored in the leakage inductance of the coupled inductor. Hence, a switch with low RDS-ON could be used. Thanks to the soft switching performance of all diodes, their reverse recovery problem is eliminated. The outstanding merits of the converter such as continuous input current and high efficiency make the presented structure a promising solution for photovoltaic applications. In the end, the proposed converter is compared to different types of DC-DC converters to prove its advantages over the converters designed before. To confirm the converter’s performance and theoretical analysis, a 200 W laboratory prototype is implemented that steps up an input voltage of 25 V to an output voltage of 400 V at the switching frequency of 50 kHz. Experimental results are illustrated. At the end, the experimental results are presented to validate the analyses conducted.